The syndrome of gastric hypertonia vague silent cadio aortitis and aortic lesions - Monge, Carlos (1923)
It is a fact well demonstrated that diseases of the heart and the aorta leading to gastric disturbances whose pathogenesis is explained by circulatory disturbances occurring in the digestive tract.